Sensory dysregulation in tic disorders is associated with executive dysfunction and comorbidities. Issue 12 (10th September 2019) - Soler, Nicolette; Hardwick, Chris; Perkes, Iain E.; Mohammad, Shekeeb S.; Dossetor, David; Nunn, Kenneth; Bray, Paula; Dale, Russell C.
Abstract: Background: Tics are conceptualized as a sensorimotor phenomenon with a premonitory urge typically described by patients. As observed in other neurodevelopmental disorders, we have observed sensory dysregulation symptoms, such as tactile hypersensitivity to clothing, in children with tic disorders; however, formal clinical research in this area is limited. Objective: To define the presence of sensory dysregulation symptoms in tic disorders, and their clinical associations. Methods: Prevalence of sensory dysregulation in 102 children with tic disorders was compared to 61 age‐ and sex‐matched healthy controls. Sensory dysregulation, executive function, and quality of life data were obtained through the Short Sensory Profile‐2, Sensory Profile‐2, Sensory Processing Measure, Behaviour Rating Inventory of Executive Function‐2, and Strength and Difficulties Questionnaire and Pediatric Quality of Life Inventory. Tics were assessed with the Yale Global Tic Severity Scale. Results: Children with tics, in the presence of comorbidity, had elevated sensory dysregulation compared to healthy controls ( P  < 0.001). There was a positive correlation between sensory dysregulation and global executive difficulties in children with tics and comorbidity (n = 87; rho = 0.716; P  < 0.001) and a negative correlation of sensory dysregulation with quality of life (n = 87; rho = –0.595; P  < 0.001). In children with tics, there was an association between sensory dysregulation and number of comorbidities ( P  < 0.001). Conclusion: In the presence of comorbidity, children with tic disorders have broad sensory dysregulation symptoms beyond the premonitory urge. There was a statistically significant association between sensory dysregulation and executive function difficulties and the presence of neurodevelopmental and psychiatric comorbidity. Sensory dysregulation can be considered neurodevelopmental symptoms, providing insight into the neurobiology of tics and opportunities for therapeutic intervention. © 2019 International Parkinson and Movement Disorder Society